2016
DOI: 10.5152/turkpediatriars.2016.3383
|View full text |Cite
|
Sign up to set email alerts
|

The effect of vitamin D on lower respiratory tract infections in children

Abstract: Aim: Lower respiratory tract infections including mainly pneumonia represent an important public health problem leading to high mortality and mobidity rates in children aged below five years in developing countries including our country. Vitamin D deficiency has been associated with increased risk of rickets/osteomalacia, various cancers, autoimmune diseases, hyperproliferative skin diseases, cardiovascular system diseases and infectious diseases. Vitamin D has an important role in cellular and humoral immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
4
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 22 publications
2
25
4
3
Order By: Relevance
“…All of them were found to be deficient in vitamin D. In contrast to our study, Tuğba Şişmanlar et al found no significant difference in vitamin D levels between the patient and control groups in their study. 22 It is important to note that all children included in this study were treated on outpatient basis. Authors also found high prevalence of vitamin D deficiency and insufficiency in both groups when compared to the previous studies conducted in their country and in the world.…”
Section: Discussionmentioning
confidence: 99%
“…All of them were found to be deficient in vitamin D. In contrast to our study, Tuğba Şişmanlar et al found no significant difference in vitamin D levels between the patient and control groups in their study. 22 It is important to note that all children included in this study were treated on outpatient basis. Authors also found high prevalence of vitamin D deficiency and insufficiency in both groups when compared to the previous studies conducted in their country and in the world.…”
Section: Discussionmentioning
confidence: 99%
“…The determination of a preventable risk factor such as vit D deficiency and initiation of the effective intervention is quite important in the management of LRTIs in children. In our country, vit D deficiency and LRTIs are common health problems in preschool children (17). The discovery that most tissues and cells in the body have a vit D receptor and the ability to convert the primary circulating form of vit D to the active form has provided new insights into the function of this vitamin (18).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in another study from Turkey, no significant differences in terms of 25(OH)D concentrations and disease severity was found between cases with lower respiratory tract infection (LRI) < 5 years of age and healthy children. However, the rates of vitamin D deficiency and insufficiency were high in both groups (25 and 22%, respectively), leading the authors to recommend routine screening for vitamin D deficiency in children with LRI, and vitamin D supplementation in all children, especially during the winter months [75]. Similarly, one study in Canada and one in Iran found no significant differences between cases and controls in terms of 25(OH)D serum levels for uncomplicated ALRI (primary viral bronchiolitis) in children less than 2 years old [76,77].…”
Section: Evidencementioning
confidence: 99%